Utility of SIRS criteria and QSOFA score in identifying patients with central nervous system infections at risk for poor outcome - Resok, Yannick C.; Olie, Sabine E.; Jellema, Korné; van de Beek, Diederik; Brouwer, Matthijs C. (Scientific reports, 2025)
Several scoring methods have been developed to identify critically ill patients with suspected sepsis who may benefit from intensive care treatment. We studied the prognostic value of the Systemic Inflammatory Response Syndrome (SIRS) criteria and the quick Sequential related Organ Failure Assessment (qSOFA) score in patients with (suspected) central nervous system (CNS) infections. We included adult patients from two prospective cohort studies consisting of (1) patients who underwent a lumbar puncture for the suspicion of a CNS infection and (2) patients with confirmed bacterial meningitis. The primary outcome was Intensive Care Unit (ICU) admission. We calculated sensitivity, specificity, and area under the curve (AUC) for the SIRS score of > 2 and a qSOFA of > 2. From April 2007 to May 2022, 629 patients with a suspected CNS infection, and 326 patients with a bacterial meningitis were evaluated. 78 of 629 (12%) episodes with a suspected CNS infection were admitted to the ICU, and 197 of 326 (60%) with bacterial meningitis. The SIRS criteria showed a sensitivity of 81% (95%CI 70–89%) with a specificity of 48% (95%CI 44–52%) in patients with suspected CNS infection. Sensitivity of the qSOFA score was 67% (95%CI 55–77%) with a specificity of 82% (95%CI 78–85%) in the same cohort. The SIRS criteria showed a sensitivity of 94% (95%CI 89–97%) and specificity of 9% (95%CI 5–15%) in patients with bacterial meningitis. The qSOFA score had a sensitivity of 59% (95%CI 52–66%) and specificity of 52% (95%CI 43–61%) in bacterial meningitis patients. In patients with a suspected CNS infection the qSOFA score was more accurate than the SIRS criteria as a risk stratification tool for ICU admission. SIRS criteria and qSOFA score showed a poor performance for the prediction of ICU admission in bacterial meningitis patients. The limited value of SIRS and qSOFA criteria in these patient populations should be acknowledged and use in clinical practice should be approached with caution.